Pengaruh pemberian sayur daun pepaya terhadap kelancaran produksi ASI pada ibu nifas - Aprilia, Reni; Rilyani, R; Arianti, Lidya (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Lactation is a time when a change in the breast of a mother, so that it can produce milk. Based on data from the Lampung Provincial Health Office, coverage of exclusive breastfeeding only reached 54.9%, which is below the national level, while in North Lampung district, coverage of exclusive breastfeeding in 2014 was only 42.2% and experienced a slight increase in 2015, which was 42, 3% Whereas in 2016 Exclusive ASI coverage increased by only 43.2%. This figure is far below the Regency Minimum Service Standards (SPM) target of 80%. Kotabumi II Health Center is one of the health centers with low exclusive breastfeeding coverage, which only reaches 14.6%. The purpose of this study is to determine the effect of papaya leaf administration on the smoothness of breast milk for postpartum mothers in the working area of the Kotabumi II Health Center in North Lampung Regency. The type of experimental research with the design of One Group Pretest Posttest research sample obtained by pretest and post-test. This study used a sample of 30 respondents, data analysis using a t-test. The average production of breast milk in postpartum mothers after papaya leaf vegetables were given to 30 breastfeeding mothers, with a mean of 4.83 standard deviations of 1.020 standard error of 0.186 and min-max value of 3-7 and after being given papaya leaves with a mean of 7, 40 standard deviations of 0.855 standard errors of 0.156 and min-max values of 5-8, with a difference of 2 mean differences of 2.57, standard deviation of 1.277, standard errors of 0.233. The p-value is 0,001 (less than 0.05). It means that there is an effect of giving papaya leaf to smooth milk in postpartum mothers in Kotabumi II Public Health Center, North Lampung Regency in 2019, suggestions for breastfeeding mothers to be able to utilize leafy papaya vegetables as a complementary therapy to facilitate breast milk production.